2020
DOI: 10.2217/bmm-2019-0378
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Vesicoureteral Reflux: An Overview

Abstract: Aim: This article aimed to review the role of cytokines, chemokines, growth factors and cellular adhesion molecules as biomarkers for vesicoureteral reflux (VUR) and reflux nephropathy (RN). Methods: We reviewed articles from 1979 onward by searching PubMed and Scopus utilizing the combination of words: ‘VUR’ or ‘RN’ and each one of the biomarkers. Results: Genetic, inflammatory, fibrogenic, environmental and epigenetic factors responsible for renal scarring need to be better understood. TGF-β, IL-10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Other studies suggest that MCP1, TGFβ1, and VEGF may be useful in the diagnosis and monitoring of renal parenchymal fibrosis in patients with VUR. One more noninvasive marker in the diagnosis and prediction of renal scarring in children with VUR seems to be urinary NGAL [ 50 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies suggest that MCP1, TGFβ1, and VEGF may be useful in the diagnosis and monitoring of renal parenchymal fibrosis in patients with VUR. One more noninvasive marker in the diagnosis and prediction of renal scarring in children with VUR seems to be urinary NGAL [ 50 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies performed on animal models with a lack of IL-6 expression have shown that in individuals with IL-6 deficiency, bacterial colonization is more intense, with uropathogens being able to escape the innate immune response and thus promote chronic inflammation. These individuals also present more severe UTIs, more pronounced structural alterations of the renal parenchyma, and ultimately, higher mortality rates [ 50 , 51 ].…”
Section: Urinary Tract Infections and Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified the differences in urine exosomal protein profiles between VUR and non-VUR patients and revealed that exosomal VTN could be used as a potential marker in predicting disease progression in patients with NGB. At present, there are no recognized non-invasive, effective biochemical indicators to predict urinary reflux ( 25 ). The present results demonstrated that urine exosomal VTN may be an early biomarker for monitoring VUR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that KIM-1 and MCP-1 in urinary can re ect the severity of kidney injury and brosis. [14][15][16] Before surgery and 6 months after surgery, urological ultrasound was routinely performed to investigate anteroposterior diameter of hydronephrosis and distal ureter diameter, voiding cystourethrography to investigate the grade of re ux, dimercaptosuccinic acid to investigate the formation and grade of renal scar, and renal function status. The levels of KIM-1 and MCP-1 in morning urine were detected to evaluate the progression of renal injury and brosis.…”
Section: Patientsmentioning
confidence: 99%